Role of Supply Chain-e Collaboration on Supply Chain Performance of Indonesian Service Sector - Prawira, Afghan; Kuraesin, Uning; Hertina, Dede; Zainudin, Zalina (ExcelingTech, 2019)
The study is aimed to examine the effect of SCEC on SCP on Indonesian service sector alongside the mediating role of SIS and SCC. This was done quantitatively 96 employees were selected as a sample size. Irregular inspecting technique and 5point Likert scale was used to collect the information. AMOS and SPSS has been used to analyze the information. The conclusion of this investigation revealed that Indonesian organizations can enhance their SCP through SCEC. The investigation further confirmed that the capacity of organizations to efficiently and completely share their thoughtful and critical information that can advance the enactment of an organization just as of the whole SC.